2004
DOI: 10.1152/ajplung.00019.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke induces MUC5AC mucin overproduction via tumor necrosis factor-α-converting enzyme in human airway epithelial (NCI-H292) cells

Abstract: Chronic obstructive pulmonary disease (COPD) is one of the leading causes of death in the U.S. Because cigarette smoking is so importantly implicated in the pathogenesis of COPD and because mucus hypersecretion plays such an important role in COPD, understanding of the mechanisms of smoking-induced mucus hypersecretion could lead to new therapies for COPD. Cigarette smoke causes mucin overproduction via EGF receptor (EGFR) in airway epithelial cells, but the cellular mechanism remains unknown. Airway epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
168
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(183 citation statements)
references
References 38 publications
10
168
3
1
Order By: Relevance
“…MUC5B is primarily secreted by submucosal glands, but also by airway goblet cells (2,3), and is thought to play mostly a protective role. In contrast, MUC5AC, which is exclusively produced by goblet cells (4), has been thought to play more of a pathologic role because of greatly increased MUC5AC expression with disease states (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…MUC5B is primarily secreted by submucosal glands, but also by airway goblet cells (2,3), and is thought to play mostly a protective role. In contrast, MUC5AC, which is exclusively produced by goblet cells (4), has been thought to play more of a pathologic role because of greatly increased MUC5AC expression with disease states (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Cigarette smoke is also an important environmental stimulus for generating ROS (87). One group has shown that ROS generation from NE and cigarette smoke leads to EGFR activation, through the activation of TNF-α-converting enzyme (TACE), to cleave pro-TGF-α from the membrane into the active soluble form of TGF-α (74,88). Because dual oxidases are expressed in airway epithelial cell surface, dual oxidase-1 (Duox-1) may be involved in TACE activation (78).…”
Section: Transcriptional Activation Of Muc5ac Through Epidermal Growtmentioning
confidence: 99%
“…Thus, activation of TACE may trigger a number of reactions participating in the promotion of neutrophil inflammation in the airways. In addition, TACE/ TGF-a/EGFR signalling also regulates mucin production, which contributes to exacerbation of asthma, COPD and CF along with neutrophilia [3,24,[59][60][61].…”
Section: Discussionmentioning
confidence: 99%